2018
DOI: 10.7717/peerj.6059
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of social-genetic relationships in the socially monogamous pied flycatcher (Ficedula hypoleuca) breeding in Western Siberia

Abstract: We explored the genetic background of social interactions in two breeding metapopulations of the pied flycatcher (Ficedula hypoleuca) in Western Siberia. In 2005, we sampled blood from birds breeding in study areas located in the city of Tomsk and in a natural forest 13 km southward of Tomsk (Western Siberia, Russia). We sampled 30 males, 46 females, 268 nestlings (46 nests) in the urban settlement of pied flycatcher, and 232 males, 250 females, 1,485 nestlings (250 nests) in the woodland plot. DNA fingerprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 65 publications
(90 reference statements)
0
17
0
Order By: Relevance
“…Flycatchers form a pair bond for the current breeding season and change social partners with each subsequent reproduction event (serial monogamy). Some individuals have polygamous relationships within one breeding season ( Grinkov et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Flycatchers form a pair bond for the current breeding season and change social partners with each subsequent reproduction event (serial monogamy). Some individuals have polygamous relationships within one breeding season ( Grinkov et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Males were caught feeding their nestlings at the age of 9‒11 days. More detailed information about the monitoring scheme of the population, the frequency of bird catching, their treatment, as well as a detailed description of the research area can be found in our earlier publication ( Grinkov et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations